Desarrollo de diagramas en Simulink de matlab para el modelamiento y simulación de tres sistemas dinámicos de primer orden - Fernández Pinche, Jholey Petterson (2024)
The main objective of the present work of thesis was: Developing the block diagrams in Simulink of Matlab that allow accomplishing the shaping and simulation of three first-rate dynamic systems: control of level of liquid in a tank, thermic process and mixing process. In the present investigation, a revision of the necessary mathematics (transformed of Laplace and transformed inverse of Laplace) to solve the referent models to the dynamic systems has come true; straightaway, a revision of the programming environment in Simulink of Matlab was done and from now on developed the block diagrams in Simulink of Matlab that repay to each one of the three mentioned dynamic systems; finally, came true the simulation of these dynamic systems, determining the values of the motionless profit, time constant and final value of the variable of exit, which worked out for the control of level of liquid in a tank: = 20 s/m2, = 251.3 s y ℎ = 3 m; thermic process: = 20 s.°C/kg, = 367.5 s y L = 78.84 °C and mixing process: = 1 dimensionless, = 5 min and = 0.11 kg/L. In conclusion, it has been checked that the diagrams that have had total success in Simulink of Matlab, for the three mentioned dynamic systems, are honest, since when has compared the graphics of the gotten-out variable, obtained by means of Simulink of Matlab and Wolfram Mathematica 10.4, it was observed that they are identical. This way it is coming true with the realistic general and trying the general hypothesis.